Family violence: Causes and its effects - Analytical social study (Journal of the College of Education for Women, 2019)
The aim of this study is to investigate the main causes of the family violence and itssocial effects.The study reveals that main factors causes of the violence are interaction betweenmulti-factors.The study shows that the poverty, low educational level, house crowded, large familysize, all of these variables causes of the violence, and then causes of family disorganizationand juvenile delinquency.The study contain of three sections:First: Focused on the causes of the violence.Second: The interaction between multi factors.Third: Social effects of family violence.